FRI0258 Improvement of Cell Cholesterol Trafficking-Related Lipoprotein Functions in Rheumatoid Arthritis Patients Treated with Adalimumab. (10th June 2014) - Ronda, N.; Greco, D.; Adorni, M.P.; Zimetti, F.; Favari, E.; Borghi, M.O.; Hollan, I.; Hjeltnes, G.; Mikkelsen, K.; Meroni, P.L.; Bernini, F.
Abstract : Background: RA is associated with accelerated atherosclerosis. HDL in RA have reduced capacity to promote cell cholesterol efflux (CEC) while LDL have increased cholesterol loading capacity on macrophages (CLC). Inflammation and immune disturbances are among the mechanisms proposed. Anti-TNFa agents appear to reduce cardiovascular risk in RA, but their effects on serum lipid profile is variable. Objectives: We studied modifications of lipoprotein function with respect to cell cholesterol trafficking after adalimumab therapy in RA. Methods: Serum was drawn from 56 patients with RA, 34 treated with methotrexate (MTX), 22 starting with adalimumab in addition to ongoing MTX (MTX/ADA), before and after 6 weeks and 6 months of treatment. We measured: serum lipid profile; CLC with cholesterol measurement by fluorimetric technique; CEC with radioisotopic technique. Results: HDL, LDL and total cholesterol serum levels increased in the MTX group after treatment, while HDL levels only increased in the MTX/ADA group. CLC significantly decreased after treatment in the MTX/ADA group only (mean ± SE, 7.16±0.28 vs 7.92±0.48 mg cholesterol/mg protein, p<0.05). In MTX group ATP-binding cassette G1 (ABCG1) and Scavenger receptor-BI (SR-BI)-mediated CEC increased after treatment; in MTX/ADA group SR-BI-mediated CEC increased. No modifications in ATP-binding cassette A1-mediated CEC occurred in either MTX or MTX/ADA group. Conclusions: Adalimumab addition to MTX treatment results in decreased cell cholesterol loading serum capacity and slight improvement in HDL promotion of cell cholesterol efflux, both potentially inhibiting foam cell formation. These effects may be especially relevant in RA patients with aggressive disease needing anti-TNFa, particularly prone to accelerated atherosclerosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2441